Buddha mind - Christ mind : a Christian commentary on the Bodhicaryāvatāra - Schmidt-Leukel, Perry (Christian commentaries on non-Christian sacred texts., 2019)
The Bodhicaryavatara ("Entering the Course towards Awakening") is an Indian Mahayana Buddhist companion to the path of a Bodhisattva, someone motivated by the altruistic "spirit of awakening". Unlike many other Buddhist scriptures, much of this text is written in the very touching form of personal reflections. Despite its late composition (7th-8th cent. CE), the Bodhicaryavatara quickly gained widespread recognition and high appraisal in various parts of the Buddhist world and even beyond. Today it is one of the most widely translated Buddhist texts. The 14th Dalai Lama has emphasized the special impact of this scripture on his own spirituality, and a number of Western scholars have praised it as a true gem among the world's religious classics. After many commentaries by Buddhist scholars throughout the centuries, this is the first commentary from a Christian perspective, exploring the deep resonances between the "spirit of awakening" and the "spirit of Christ" --